Aging, disability and frailty - Topinková, Eva (Annals of nutrition & metabolism, 2008)
Despite multiple and often overlapping definitions of disability and frailty, both are common clinical characteristics of aged individuals though not identical. The geriatric syndrome of frailty is described as status of global impairment of physiological reserves involving multiple organ systems. The clinical correlate of frailty manifests as increased vulnerability, impaired capability to withstand intrinsic and environmental stressors, and limited capacity to maintain physiological and psychosocial homeostasis. Geriatric frailty is found in 20-30% of the elderly population over 75 years and increases with advancing age. It was reported to be associated with long-term adverse health-related outcomes - increased risk of geriatric syndromes, dependency, disability, hospitalization, institutional placement, and mortality. The clinical phenotype of frailty manifests as multi-system pathologies characterized by low physical activity, global weakness with low muscle strength, fatigability/exhaustion, overall slowness particularly of gait, loss of weight among others. These above-mentioned clinical symptoms could be explained by (or related to) some 'preclinical' diagnoses such as sarcopenia, osteopenia, nonspecific balance disorders, nutritional problems, and overall deconditioning. More recent studies found the frailty clinical phenotype to be associated with pathologic laboratory markers (IL-6, CRP, 25-hydroxyvitamin D, IGF-1, D-dimers), which suggest possible pathogenesis involving hormonal dysregulation, immuno-aging, pro-coagulation and pro-inflammatory status. In the article, current recommendations for future research strategies of frailty syndrome will be discussed.
Keywords: senioři; únava; činnosti denního života; Aging; Prevalence; Weight Loss; Nutritional Status; senioři nad 80 let; Male; svalová slabost; postižení; mužské pohlaví; prevalence; Fatigue; Activities of Daily Living; fenotyp; Persons with Disabilities; Aged, 80 and over; stárnutí; Phenotype; ženské pohlaví; Humans; Muscle Weakness; hmotnostní úbytek; Health Status; ukazatele zdravotního stavu; Frail Elderly; Health Status Indicators; zdravotní stav; nutriční stav; Aged; Female; lidé; křehký senior